Trends in accessibility of negotiated targeted anti-cancer medicines in Nanjing, China: An interrupted time series analysis - Liu, Yanyan; Yi, Huining; Fang, Kexin; Bao, Yuwen; Li, Xin (Frontiers in Public Health, 2022)
Background In order to establish a long-term strategy for bearing the costs of anti-cancer drugs, the state had organized five rounds of national-level pricing negotiations and introduced the National Health Insurance Coverage (NHIC) policy since 2016. In addition, the National Healthcare Security Administration (NHSA) introduced the volume-based purchasing (VBP) pilot program to Nanjing in September 2019. Taking non-small cell lung cancer as an example, the aim of the study was to verify whether national pricing negotiations, the NHIC policy and the VBP pilot program had a positive impact on the accessibility of three targeted anti-cancer drugs. Methods Based on the hospital procurement data, interrupted time series (ITS) design was used to analyze the effect of the health policy on the accessibility and affordability of gefitinib, bevacizumab and recombinant human endostatin from January 2013 to December 2020 in Nanjing, China. Results The DDDs of the three drugs increased significantly after the policy implementation (P < 0.001, P < 0.001, P = 0.008). The trend of DDDc showed a significant decrease (P < 0.001, P < 0.001, P < 0.001). The mean availability of these drugs before the national pricing negotiation was <30% in the surveyed hospitals, and increased significantly to 60.33% after 2020 (P < 0.001, P = 0.001, P < 0.001). The affordability of these drugs has also increased every year after the implementation of the insurance coverage policy. The financial burden is higher for the rural patients compared with the urban patients, although the gap is narrowing. Conclusion The accessibility of targeted anti-cancer drugs has increased significantly after the implementation of centralized prices, the NHIC policy and the VBP pilot program, and has shown sustained long-term growth. Multi-pronged supplementary measures and policy approaches by multiple stakeholders will facilitate equitable access to effective and affordable anti-cancer drugs.